Tuning features of H-bonded layer by layer assembly of poly(4-vinyl pyridine) and carboxylated poly-(2, 3, 4, 5, 6-pentafluorostyrene) synthesized through para-fluoro-thiol reaction. (August 2019) - Yin, Quanyi; Beyou, Emmanuel; Portinha, Daniel; Charlot, Aurélia
Graphical abstract: Highlights: Mercapto-propionic acid was grafted onto PPFS by para-fluoro-thiol reaction. The extent of modification of PPFS was tuned by the reactional parameters. The ability of PPFS-based copolymers to develop H-bonds with P4VP was studied. H-bonded LbL films were successfully prepared. The growth mechanism of the LbL assembly was fully investigated. Abstract: Para-fluoro-thiol reaction (PFTR) was applied to poly(2, 3, 4, 5, 6-pentafluorostyrene) (PPFS) with mercaptopropionic acid (MPA), resulting in a library of carboxylated-PPFS copolymers (PPFS-MPA) differing in their chemical composition. The ability of these COOH-containing derivatives to develop H-bonds with poly(4-vinyl pyridine) (P4VP) in solvent solution was investigated, and it was shown that the extent of the H-bonded complexes was closely influenced by the degree of PPFS modification and by the nature of solvent. Subsequently, the Layer by Layer stepwise deposition of P4VP and PPFS-MPA was achieved from various deposition solvents. It was demonstrated that the use of DMF as solvent does not allow for the formation of LbL films, due to its competitive H-bond acceptor character. In contrary, when solvents such as CHCl3 and MEK are respectively utilized for P4VP and PPFS-MPA, thick (P4VP/PPFS-MPA)-based LbL films constituted of interpenetrated layers are obtained and the topography is smooth and rather featureless. The use of ethanol as deposition solvent for both P4VP and PPFS-MPA leads to very thin films made of well-stratified polymer layers, with a nodular and patchy surface morphology.